2015
DOI: 10.1038/nprot.2015.012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and use of an asymmetric transfer hydrogenation catalyst based on iron(II) for the synthesis of enantioenriched alcohols and amines

Abstract: The catalytic hydrogenation of prochiral ketones and imines is an advantageous approach to the synthesis of enantioenriched alcohols and amines, respectively, which are two classes of compounds that are highly prized in pharmaceutical, fragrance and flavoring chemistry. This hydrogenation reaction is generally carried out using ruthenium-based catalysts. Our group has developed an alternative synthetic route that is based on the environmentally friendlier iron-based catalysis. This protocol describes the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Iron-catalyzed TH has kept growing in the last 5 years, and great progress has been achieved. 275 After their pioneering study on TH based on iron catalysts containing PNNP backbones, in 2010 Morris' group 276,277 prepared a series of new iron (II) precatalysts trans-[Fe(Br)-(CO)(PPh 2 CH 2 CHNCHRCHRNCHCH 2 PPh 2 )][BPh 4 ] with diamines containing various substituents through a onepot synthetic route. These authors found that all of them showed excellent catalytic properties in the ATH of acetophenone with 2-PrOH and KO t Bu under mild conditions.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…Iron-catalyzed TH has kept growing in the last 5 years, and great progress has been achieved. 275 After their pioneering study on TH based on iron catalysts containing PNNP backbones, in 2010 Morris' group 276,277 prepared a series of new iron (II) precatalysts trans-[Fe(Br)-(CO)(PPh 2 CH 2 CHNCHRCHRNCHCH 2 PPh 2 )][BPh 4 ] with diamines containing various substituents through a onepot synthetic route. These authors found that all of them showed excellent catalytic properties in the ATH of acetophenone with 2-PrOH and KO t Bu under mild conditions.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…To counteract this assumed outcome, we utilized a completely closed system known as a cannula transfer (Supplementary Figure 1) commonly used in chemical synthesis protocols. 1 In order to transfer liquids from one tube to another, the tubes have septum lids that can be punctured by long needles connected to each other via Tygon tubing. Injection of air into the liquid-containing tube increases the pressure in the tube causing the liquid to move up through the needle and tubing into the empty tube.…”
Section: Resultsmentioning
confidence: 99%
“…The above mechanism was validated by preparing amine-(imine)diphosphine (P-NH-N-P type) ligands, to show that they activate iron for the catalysis of ketones. [39][40][41] The catalyst precursors C5a-C5c showed excellent reactivity for the reduction of several ketones. Acetophenone (S1), in the presence of 0.016-0.05 mol% of complex C5c bearing large 3,5-xylyl substituents, 0.033-0.40 mol% t-BuOK, in i-PrOH as the solvent and hydrogen donor, was reduced with 90% ee and with a TOF of 100 000 h -1 at 28 o C. Complex C5a was an effective precatalyst for other more challenging substrates such as naphthyl and heteroaryl ketones.…”
Section: Scheme 1 Ath Of Ketones Catalyzed By Fe Complex C1mentioning
confidence: 99%